OPTIMIZING THE TOUR GUIDE'S PROVISION OF INFORMATION THROUGH ONLINE MEDIA: OPTIMALISASI TOUR GUIDE DALAM PEMBERIAN INFORMASI MELALUI MEDIA ON-LINE - Yulianto, Irwan; Alvianna, Stella; Pandu Dinata, Krishna; Luisa Stefani, Agnes (Faculty of Vocational Studies, Universitas Airlangga, 2024)
Background: Tour guides play a crucial role during a vacation. Tour guides do more than only provide information about the tourist spots seen; they also educate foreign tourists who visit an area. The number of travel agents supplying guidance is growing, and they come in a variety of forms, including companies, institutions, individuals, and communities. Objective: This activity tries to solve marketing difficulties (by generating online marketing media) while also giving tourist training, particularly for tour guides, to community members. Method: This activity tries to solve marketing difficulties (by generating online marketing media) while also giving tourist training, particularly for tour guides, to community members. Results: The presence of a website/blog will enhance the number of users or consumers who use the services provided by the